(untitled) (Research, Society and Development, 2021)
Objective: Use of a band-loop space maintainer in the early loss of a primary tooth. Methodology: Based on the patient’s permission through the Informed Consent Form (FICF) to share their image for the proper purpose, this study is a clinical case report of a descriptive analytical nature (Pereira et al., 2018). Clinical Case Report: Patient L.S.S.R., 4 years old, female, black, attended the dental clinic at Centro Universitário Fametro accompanied by her parents. During anamnesis, the guardian reported the presence of pain in element 74 as the main complaint. In the first consultation, the guardian found that the patient was suffering from asthma and anemia. Regarding food, one patient drank pure and porridge from a bottle, brushed milk three times a day, however, he was not in the habit of flossing. It was also created that a patient had the habit of sucking a pacifier until the age of three. Then, prophylaxis, clinical examination and periapical radiography of elements 55 and 74 were performed. Final Considerations: Rehabilitation in unilateral loss of the deciduous first molar with the use of the band-loop space maintainer is effective in its results, preventing mesialization adjacent tooth and preserving space for proper eruption of permanent successor teeth.